Boosting Profitability Through Green Finance, CSR, and Capital Structure: The Moderating of The Board of Directors - Amiarti, Dela; Fahruna, Yulyanti; Wendy; Giriati; Mustaruddin (Ilomata International Journal of Management, 2025)
This study aims to examine the effects of implementing green finance, corporate social responsibility (CSR), and capital structure on profitability, with the board of directors as a moderating variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The combination of green finance with corporate social responsibility (CSR) in this study is uncommon in previous studies. In this case, green finance is more concerned with the environment, whereas corporate social responsibility (CSR) is more focused on social issues. Conducted as a quantitative study, the sample selection employed purposive sampling. Secondary data was collected from annual reports and sustainability reports, accessed via www.idx.co.id and the respective companies' official websites The study’s findings reveal that green finance does not significantly impact profitability, while CSR has a positive and significant effect on profitability. Capital structure, on the other hand, has a significant negative impact on profitability. As a moderating variable, the board of directors does not moderate the relationship between green finance and profitability. However, it weakens the positive impact of CSR on profitability and strengthens the negative impact of capital structure on profitability. The implications of this study provide empirical insights into the influence of green finance, CSR, and capital structure on profitability levels. Additionally, the interaction effect analysis suggests that the board of directors plays a strategic role in decision-making related to resource allocation with a sustainability orientation.